Characterization of geometric variance in the epithelial nerve net of the ctenophore Pleurobrachia pileus. Issue 9 (12th January 2022) - Courtney, Amy; Liegey, Jérémy; Burke, Niamh; Hassett, Amy R.; Lowery, Madeleine; Pickering, Mark
Abstract: Neuroscience lacks a diverse repertoire of model organisms, resulting in an incomplete understanding of the general principles of neural function. Ctenophores display many neurobiological and experimental features which make them a promising candidate to fill this gap. They possess a nerve net distributed across their body surface in the epithelial layer. There is a long‐held assumption that nerve nets are "simple" and lack distinct organizational principles. We want to challenge this assumption and determine how stereotyped the structure of this network is. We estimated body surface area in Pleurobrachia pileus using custom optical projection tomography and light sheet morphometry imaging systems. Using an antibody against tyrosinated α‐tubulin, we visualized the nerve net in situ and quantified the geometric properties using an automated segmentation approach. We characterized organizational rules of the epithelial nerve net in animals of different sizes and at different regions of the body. We found that specific morphological features within the nerve net are largely unchanged during growth. These properties must be essential to the functionality of the nervous system and therefore are maintained during a change in body size. We have also established the principles of organization of the network and showed that some of the geometric properties are variable across different parts of the body. This suggests that there may be different functions occurring in regions with different structural characteristics. This is the most comprehensive structural description of a ctenophore nerve net to date and demonstrates the amenability of P. pileus for whole organism network analysis. Abstract : This work provided a statistical description of a ctenophore nerve net at different anatomical regions, in animals of different sizes, to elucidate the rules of organization of one of the first nervous systems.